Multifocal Multisystem Langerhans Cell Histiocytosis Involving Pituitary Masquerading as Crohn’s Disease: A Case Report and Review of the Literature - Mohd. Ashraf Ganie; Bhanu Malhotra; Manpreet Saini; Arshiya Dutta; Atul Sharma; Kim Vaiphie; Pinaki Dutta (Case Reports in Endocrinology)
Background/Objective. We present a case of Langerhans cell histiocytosis (LCH) with gastrointestinal involvement masquerading as inflammatory bowel disease (IBD) in a patient who initially had features of central diabetes insipidus (CDI). Case Report. A 19-year-old male presented at 14 years of age with central diabetes insipidus. He subsequently developed panhypopituitarism and sellar-suprasellar mass, the biopsy of which was inconclusive. Secondary causes for hypophysitis were ruled out. Five years later, he developed perianal pus discharging sinuses, positive ASCA, and sacroiliitis. Rectal ulcer biopsy showed nonspecific inflammation and necrosis. Hence, he was managed as inflammatory bowel disease (IBD). Due to nonresponsiveness of symptoms, doubt about diagnosis was invoked and rectal ulcer biopsy was repeated, which then showed infiltration by Langerhans cells. Hence, he was diagnosed with LCH and showed resolution of symptoms on initiating steroids and vinblastine. Discussion. Gastrointestinal involvement by LCH is unusual and only rarely has represented a prominent clinical manifestation. In most cases, such involvement suggests widespread multisystem disease. Its distinctive morphologic and immunohistochemical features allow LCH to be distinguished from other inflammatory infiltrations found in mucosal biopsy specimens. Conclusion. Preceding CDI and hypopituitarism may predict LCH in patients with IBD-like diseases.